94 Effect of Forage Type and Supplement Frequency on Heifer Growth and Reproductive Performance. (1st March 2018) - Hersom, M J; Yelich, J V
Abstract: In each of 2 yr a 2 by 2 factorial design of forage type Tifton-85 or Coastal bermudagrass large round bale silage and supplement frequency of daily or 3 d/wk (3X) was used to evaluate growth and reproductive performance in heifers. In each year, heifers (n = 123, BW = 272 ± 3.7 kg) were blocked by breed, BW, and BCS and randomly assigned to 1 of 4 pens (15 heifers/pen) for a 112 d development period. Heifers were pen fed silage and supplement fed daily or 3X, mean amount was 2.96 kgheifer -1 d -1 . Weekly blood samples were collected for analysis of plasma progesterone concentration. Heifer BW and BCS were collected every 28 d. On d 112, heifers were synchronized using a CIDR and time-AI. Ten d following AI, heifers were exposed to a bull for 60-d. Pregnancy status was determined at 30 and 60 d intervals. Statistical analysis used pen as the experimental unit and PROC MIXED to analyze BW, BCS, and GENMOD for reproductive performance. Fixed effects included forage, frequency, and interactions, random effects included year and heifer. Final BW and 112-d ADG were not different ( P > 0.31) for Coastal than Tifton-85 (351 vs 345 ± 7.4 kg and 0.69 vs 0.65 ± 0.11 kg/d). Final BW and 112-d ADG did not differ ( P > 0.84) between Daily and 3X supplemented heifers (348 vs 348 ± 4.8 kg and 0.67 vs 0.68 ± 0.12 kg/d). There was no forage x frequency interaction ( P = 0.20) for final BW and 112-d ADG. Body condition score on d 112 did not differ ( P > 0.05, 5.4 ± 0.11). Cycling status at the initiation of the breeding season tended ( P = 0.10) to be greater for Daily (46%) compared to 3X (31%) heifers. Artificial insemination pregnancy exhibited a forage x frequency interaction ( P < 0.009). Tifton-85/daily supplemented heifers (73%) had similar ( P > 0.05) AI pregnancy rate compared to Coastal/3X (55%), but greater ( P < 0.05) than Tifton-85/3X (42%) and Coastal/daily (39%). Coastal/3X and Tifton-85/3X both had greater ( P < 0.05) AI pregnancy rate than Coastal/daily. However, 30-d and 60-d pregnancy rates did not differ ( P > 0.05) among treatments (73% and 85%, respectively). Similarities in heifer final BW and ADG among forage types and supplement frequency resulted in similar heifer 30-d or 60-d pregnancy rate. However, Tifton-85 did result in greater 30- and 60-d pregnancy rates.